A review of joint attention and social‐cognitive brain systems in typical development and autism spectrum disorder. (25th October 2017) - Mundy, Peter
Abstract: This article provides a review of the increasingly detailed imaging literature on the neurodevelopment of joint attention. Many findings from this literature support and inform the hypothesis that the neurodevelopment of joint attention contributes to the functional development of neural systems for human social cognition. Joint attention begins to develop by 5 months of age and is tantamount to the ability to adopt a common perspective with another person. It involves a whole‐brain system with nodes in the: (a) dorsal and medial frontal cortex, (b) orbital frontal/insula cortex, (c) anterior/posterior cingulate cortex, (d) superior temporal cortex, (e) precuneus/parietal cortex, and (f) amygdala and striatum. This system integrates triadic information processing about (a) self‐attention/action, (b) information about others' attention/action during social interactions that involve, (c) coordinated attention as well as processing a common referent in space. The results of this new imaging literature have the potential to advance current models of social cognition and the social brain, which rarely consider the contribution of the cognitive neurodevelopment of joint attention. The new neuroscience of joint attention is also extremely valuable for clinical research on social‐cognitive neurodevelopmental disorders. This is most clearly the case for autism spectrum disorder (ASD) because it is consistent with the hypothesis of substantial functional neurodevelopmental continuity between the preschool impairments of joint attention, and childhood theory of mind ability that characterizes the development of ASD. Abstract : A new view of social‐cognitive neurodevelopment is emerging from imaging studies of joint attention. Theory and these studies suggest that the cortical systems that develop to support joint attention in infancy play a major role in the subsequent development of social‐cognitive mentalizing. These studies also support the hypothesis that an impairment of joint attention in the first two years of life is fundamental to atypical social‐cognitive neurodevelopment in autism spectrum disorders.